2010
DOI: 10.1002/esp.1946
|View full text |Cite
|
Sign up to set email alerts
|

Forest fire, bank strength and channel instability: the ‘unusual’ response of Fishtrap Creek, British Columbia

Abstract: In August 2003, the McLure forest fi re burned 62% of the drainage basin of Fishtrap Creek. Streamfl ow has been measured there since the early 1970s, and suspended sediment concentration and channel morphology have been monitored since the fi re. Although the short post-fi re period (four years) limits our ability to draw fi rm conclusions about streamfl ow changes, there has been no obvious increase in peak fl ows since the fi re. However, the total runoff during the freshet period does appear to have increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…In Fishtrap watershed, there was limited evidence of mass movement events and gully erosion, and it is concluded that erosion of channel banks represents the main process contributing fine (and coarse) sediment to the creek. This finding is corroborated by the work of Eaton et al (2010a) on the channel bank dynamics of Fishtrap Creek, which has documented significant channel bank erosion and channel migration due to root decay and a lack of vegetative root strength 3-5 years following the wildfire.…”
Section: Sediment Response Of Fishtrap Watershed To the Wildfiresupporting
confidence: 57%
See 4 more Smart Citations
“…In Fishtrap watershed, there was limited evidence of mass movement events and gully erosion, and it is concluded that erosion of channel banks represents the main process contributing fine (and coarse) sediment to the creek. This finding is corroborated by the work of Eaton et al (2010a) on the channel bank dynamics of Fishtrap Creek, which has documented significant channel bank erosion and channel migration due to root decay and a lack of vegetative root strength 3-5 years following the wildfire.…”
Section: Sediment Response Of Fishtrap Watershed To the Wildfiresupporting
confidence: 57%
“…260 km 2 . The fire was classified as a Rank 6 fire, which is the most extreme and hazardous category of fire behaviour (Eaton et al 2010a). The Fishtrap Creek watershed (area is 158 km 2 ; 135 km 2 to the Water Survey of Canada (WSC) gauging station at 51°07′24″N, 120°12′34″W, Fig.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations